The Problems of Halal Certification Regarding Consumer Protection in Malaysia and Indonesia - Ratna Sofiana; Satria Utama; Abdur Rohim (Lembaga Contrarius Indonesia, 2021)
Halal certification is a form of the State's protection for Muslim society. Malaysia and Indonesia are two Muslim-majority countries. These two countries are concerned about providing a guarantee for the right of their people to obtain foods, drugs, and cosmetics following their Islamic beliefs. Therefore, they are to ensure halal certification as part of the efforts. In order to scrutinize the two countries' policies on halal products, this article aims to explore the problems of halal certification on consumer protection they face. This study applies a comparative approach. Data were collected by literature study in the related topics. The findings of this study conclude that, in terms of governance systems, halal certification performed by Malaysia is more organized and systematic than by Indonesia. The law enforcement of the Republic of Indonesia, compiled in Omnibus Law 2020, has a positive impact on the halal certification processes. However, it is not an appropriate guarantee of excellent governance systems due to its status after the decision of the Constitutional Court in 2020, which suspended the constitutionality of this Omnibus Law.